Analisis Volatilitas Harga Pangan di DKI Jakarta pada Tahun 2023: Pengaruh Musim Kemarau Panjang terhadap Harga Komoditas Beras dan Tingkat Inflasi Volatile Food - Fadilla, Syifa (PT Literasi Nusantara Publisher, 2025)
The prolonged drought phenomenon has significantly impacted food production and commodity price stability, particularly rice, which is a staple food for the population. This study aims to analyze the effects of drought on rice price fluctuations in DKI Jakarta and its impact on inflation rates. The research method used is a qualitative approach by collecting and analyzing data from various sources such as literature, statistical documents, and previous research reports. The study results indicate that the drought occurring from August to September 2023 led to crop failures in several regions, causing a surge in rice prices in DKI Jakarta. This price increase is attributed to various factors, including reduced production due to extreme climate conditions, limited agricultural land, and distribution sector constraints. Furthermore, data show that rising rice prices put pressure on inflation, especially in DKI Jakarta, which faces challenges in food price fluctuations due to prolonged dry seasons.